Composition and properties of drilling and completion fluids - Darley, H. C. H. (Henry C. H.), 1911-; Gray, George Robert, 1907-; Elsevier Science Publishers (Houston : Gulf Pub. Co., Book Division, 1988)
Composition and Properties of Drilling and Completion Fluids, Fifth Edition, covers the fundamental principles of geology, chemistry, and physics that provide the scientific basis for drilling fluids technology. New material for drilling, logging, and production supervisors and engineers exlains how the choice of a drilling fluid and proper maintenance can profoundly reduce total well costs. It also defines technical terms necessary to the understanding of instructions and information provided by the mud engineer. Updated chapters discuss evaluation of drilling fluid performance, clay mineralogy and colloid chemistry, rheology, filtration properties, hole stability, drilling problems, and completion fluids.
Rev. ed. of: Composition and properties of oil well drilling fluids / George Gray, H.C.H. Darley, Walter F. Rogers.
Includes bibliographies and indexes.
Keywords: Drilling muds; Completion fluids; Electronic books